Influence of meshing on the numerical simulation of liquid composite molding processes - Dong, Jonathan (Springer Netherlands, 2011)
Computer simulation has been an efficient and cost-effective tool for the Liquid Composite Molding (LCM) processes, including the RTM, VARTM, and resin infusion, compared to trial-and-error. The Control Volume Finite Element Method (CVFEM) has been the predominant method for simulation. Two critical issues of CVFEM are simulation accuracy and computational efficiency, and they are strongly dependent on meshing. In this paper, the influence of meshing on the simulation accuracy is investigated. Both uniform and non-uniform meshes are studied. The results show that for a radial flow, simulation accuracy can be significantly improved by using non-uniform meshes. A case study is conducted and it is shown that for a point injection, the computation time for mold filling simulation can be reduced by more than 99% while maintaining the same simulation accuracy.